2019
DOI: 10.1007/s10661-019-7775-7
|View full text |Cite
|
Sign up to set email alerts
|

Determining suspended solids and total phosphorus from turbidity: comparison of high-frequency sampling with conventional monitoring methods

Abstract: Suspended solids (SS) are important carriers of pollutants such as phosphorus (P) in streams, but the sampling frequency in monitoring programs is usually insufficiently frequent to capture episodic SS and total P (TP) peaks. The suitability of turbidity and conductivity as a surrogate for SS and TP was studied using 108 monitoring stations located in catchments of different sizes, land uses, and pollution levels. The use of high-frequency turbidity measurements to estimate SS and TP loads was compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…The strong positive relationships between turbidity and TP and TN suggest that turbidity values can be an effective proxy for TP and TN despite the numerous complicating factors (e.g., floc size, shape) that are known to affect turbidity measurements. Although, relatively little is known about the utility of turbidity measurements for the prediction of TP and TN in undisturbed landscapes, Villa et al (2019) suggest that turbidity readings can serve as useful proxies for TP in catchments with a substantial percentage of intensive agricultural land. Interestingly, the floc size exerted less influence in this study catchment on TP and TN concentrations since these remained between 10 and 30 μg L −1 and 0.3–0.7 mg L −1 respectively, regardless of variations in EPS ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The strong positive relationships between turbidity and TP and TN suggest that turbidity values can be an effective proxy for TP and TN despite the numerous complicating factors (e.g., floc size, shape) that are known to affect turbidity measurements. Although, relatively little is known about the utility of turbidity measurements for the prediction of TP and TN in undisturbed landscapes, Villa et al (2019) suggest that turbidity readings can serve as useful proxies for TP in catchments with a substantial percentage of intensive agricultural land. Interestingly, the floc size exerted less influence in this study catchment on TP and TN concentrations since these remained between 10 and 30 μg L −1 and 0.3–0.7 mg L −1 respectively, regardless of variations in EPS ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In situ measured turbidity (TURB) has been used as a surrogate for TP or PP in several studies (Grayson et al 1996;Hopkins et al 2017;Horsburgh et al 2010;Lannergård et al 2019;Spackman Jones et al 2011;Stubblefield et al 2007;Valkama and Ruth 2017;Villa et al 2019). Recent studies have suggested that the river nutrient load is better captured with high-frequency optical sensors than with low-frequency water sampling combined with continuous discharge data (Stutter et al 2017;Valkama and Ruth 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Turbidity is a suitable surrogate for TP only if a reasonable relationship between these constituents is found (Villa et al 2019). The physicochemical properties of suspended sediment impact the capacity of suspended solids to transport PP, which is largely site dependent and varies temporally (House and Denison 2002;Van der Perk et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The weak but significant correlations of water electrical conductivity with the analysed variables reflect the plasticity of the conductivity and the potential use that could be made as an indicator variable of important changes within the system. Among other uses, the total dissolved solids can be estimated from conductivity (Villa et al, 2019), since it is a measure of the volume of ionized solids, such as salts and minerals. Finally, the variability explained by the PCs of all the variables measured in each of the piezometers did not allow to separate the two treatments (Control versus Pennisetum), reflecting a similar consistency of all the variables throughout the flow of water within CW.…”
Section: Discussionmentioning
confidence: 99%
“…Because this is strictly linked to turbidity and total dissolved solids. According to Villa, Fölster, & Kyllmar (2019), the site turbidity and conductivity-total phosphorus relationship was significant at 78% of sites (n= 84; mean r 2 = 0,62). Other physicochemical parameters such as dissolved oxygen and oxidation-reduction potential could also be tested.…”
mentioning
confidence: 96%